In-situ ballast condition assessment by tamping machine integrated measurement system. Issue 1 (April 2021) - Barbir, O; Adam, D; Kopf, F; Pistrol, J; Antony, B; Auer, F
Abstract: The condition of the ballast bed is one of the most important parameters to be determined in order to assure a safe and economical operation of railway systems. Better knowledge of ballast condition provides an advantage in defining the optimum time for ballast bed cleaning or renewal. State of the art ballast condition quantification methods all require in-situ ballast sampling followed by laboratory tests, reducing track availability and making additional track closure necessary, thus making the determination of ballast condition a time-consuming and challenging task. The tamping process is the core maintenance activity in ballasted track and it is crucial for the economical service life of the track and essential in restoring the track geometry for safe train operations. During the tamping process, the tamping tines interact with the ballast matrix, transferring the displacement caused by the dynamic excitation to the ballast, compacting it under the sleeper. This interaction is observed and measured in-situ within the framework of a research project presented in this paper. Lateral forces and compaction energy, together with the loading and unloading response of the ballast matrix during compaction are used to determine the ballast condition. Serving as a confirmation of the ballast condition definitions made based on the in-situ measurements, a semi-analytical model of the tamping unit-ballast matrix interaction has been developed. The mechanical model is used to simulate different ballast conditions in order to optimize the ballast life cycle and improve the understanding of ballast behaviour under cyclic loading.